Efficient metformin transformation in sulfite/UV process co-present with oxygen - Gu, Yurong; Zhang, Yi; Jiang, Chengchun; Dong, Zijun; Bai, Xue (Frontiers in Environmental Science, 2023)
UV/sulfite process without oxygen has been extensively explored and used for the degradation of many micro-pollutants. In the present work, a UV/sulfite process in the presence of oxygen was applied to degrade a widely used pharmaceutical compound, metformin (MET). The results showed that the oxygen-involved UV/sulfite process could efficiently degrade MET. At an initial concentration of 2.5 mg/L, 86.0% of MET was removed from the contaminated water within 180 min irradiation at a sulfite dosage of 10 mM, solution pH of 9, and UV intensity of 4092 μW/cm2. In addition, sulfate radical (SO4∙- ), hydroxide radical (∙OH), hydrogen atom (∙H), and hydrated electron (eaq-) were found to be the dominant active species contributing to MET removal in the studied process through scavenging experiments. The increase in UV intensity, sulfite dosage, solution pH, and reaction temperature enhanced MET degradation in the investigated process to a certain extent, whereas the introduction of bicarbonate and fulvic acid slightly suppressed MET degradation. Finally, the degradation products of MET were identified. The oxygen-involved UV/sulfite process exhibited a remarkable denitrification capacity (> 80%) in MET. The findings of this study may offer a novel approach for treating emerging contaminants.